Fingerprinting Profile of Saponin Glycosides in Bacopa Monnieri (L.) Wettst: Life Sciences-Microbiology - Singh, Chhaya; Saxena, Rishi Kumar; Tripathi, Pawan; Gupta, Sonika (International Journal of Life Science and Pharma Research, 2022)
As a medhya rasayana in Ayurveda formulations, B. monnieri has undergone extensive research into its bioactive chemicals in the last few years. To date, no research has been done on the chemical profiles of different extract components, such as the leaf and stem compounds that are crucial for pre-formulation purposes. Routine B. monnieri testing requires the use of welldefined concentrations of bacopaside II and baposide A3. As a result, the study’s goal was to identify the active ingredients found in the leaves and stems of the Bacopa monnieri plant. We want to standardize phytoconstituents in B. monnieri leaves and stems using two different markers and the HPLC technique described here. The HPLC fingerprinting analysis of the extract of B. monnieri was carried out. Phosphoric acid: acetonitrile (65: 53 v/v) was used as the mobile phase, and the absorbance at 240 nm was measured after a 50-minute run time. Saponins found in the leaf extract included apigenin, bacopasaponin A, bacoside A3, and bacoside A1, with retention durations of 21.217, 17.843, 15.241, 14.540, 11.274, and 11.263, respectively. Stem extract, on the other hand, revealed the existence of major compounds such as bacopaside II, bacoside A3, bacopaside I, and bacosaponin C, with retention durations of 21.133, 14.186, 14.021, and 13.970, respectively. Phytoconstituents were found in greater abundance in the leaf extract of the plant than in the stem extract. The standard bacopaside II and bacoside A3 were used to match the phytoconstituents found in leaves and stems. HPLC fingerprinting was used to check the quality of plant extracts and their fractions, such as methanol. Keywords: ,